2008
DOI: 10.1007/s11277-008-9530-1
|View full text |Cite
|
Sign up to set email alerts
|

Range-Based Sleep Scheduling (RBSS) for Wireless Sensor Networks

Abstract: Sleep scheduling in a wireless sensor network is the process of deciding which nodes are eligible to sleep (enter power-saving mode) after random deployment to conserve energy while retaining network coverage. Most existing approaches toward this problem require sensor's location information, which may be impractical considering costly locating overheads. This paper proposes range-based sleep scheduling (RBSS) protocol which needs sensor-to-sensor distance but no location information. RBSS attempts to approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The algorithm decreased the inferior solutions and narrowed the searching range of the algorithm. In 2014, Mini et al [6] have found that the sensor deployment is done based on the area coverage [14][15][16][17][18], which yields less network lifetime. So they focused on target coverage and optimized the sensor node deployment and scheduling to achieve the maximum target coverage and increasing the network life time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The algorithm decreased the inferior solutions and narrowed the searching range of the algorithm. In 2014, Mini et al [6] have found that the sensor deployment is done based on the area coverage [14][15][16][17][18], which yields less network lifetime. So they focused on target coverage and optimized the sensor node deployment and scheduling to achieve the maximum target coverage and increasing the network life time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulation shows improved performance of DCS over full area coverage schemes. In order to prevent coverage drop and enhance the network lifetime, the authors in [11] have presented a Distributed Sleep Scheduling Algorithm with Range Adjustment (DSRA). This sleep scheduling algorithm depends upon the residual energy of the sensor node and the size of the overlap area between the sensor and its neighboring nodes.…”
Section: Related Workmentioning
confidence: 99%
“…A range-based sleep scheduling (RBSS) protocol [22] is a deterministic communication sleep program. RBSS divides running time into fixed-length time periods called rounds.…”
Section: Distributed Sleep/wake Schedulingmentioning
confidence: 99%